The Role of Libraries in the Development Information Literacy Skills and Application of Dokuz Eylul University - Saatçioğlu, Ömür; Özmen, Ömür; Sürel Özer, Pınar (Information World, 2003)
One of the areas where the impact of rapid change and developments most is the university education and libraries. Especially, technological development is one of the most important factors that affect the restructuring of university education and libraries is unavoidable. The skills that should be obtained throughout the university education carry the outmost importance in the restructuring process. One of these skills, which will make the major contribution to lifelong learning and learning how to learn, is information literacy. The role of library and librarians are increasing in the development of information literacy applications. The objective of this article is to define the development of information literacy; the changes in university education and libraries resulting from development of information literacy and to determine the position of library and librarians in the information literacy applications of Dokuz Eylul University.